2017
DOI: 10.2340/00015555-2734
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Double Fungal Infections of the Skin Caused by Phialemoniopsis endophytica and Exophiala jeanselmei in a Patient with Microscopic Polyangiitis

Abstract: is missing (Short communication).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…In Thyridium, T. endophyticum and T. curvatum have been isolated from both plants and animals (Gam and McGinnis 1983;Halleen et al 2007;Perdomo et al 2013;Su et al 2016;Ito et al 2017). There are several examples of fungal species, including human pathogens, detected from various substrates.…”
Section: Discussionmentioning
confidence: 99%
“…In Thyridium, T. endophyticum and T. curvatum have been isolated from both plants and animals (Gam and McGinnis 1983;Halleen et al 2007;Perdomo et al 2013;Su et al 2016;Ito et al 2017). There are several examples of fungal species, including human pathogens, detected from various substrates.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey in the USA in 2007, Exophiala dermatitis was the species most frequently isolated, followed by E. xenobiotica, E. lecanii‐corni , Exophiala phaeomuriformis and E. jeanselmei in that order 5 . Recently, E. xenobiotica , 6 E. lecani‐cornii , 7 Exophiala oligospermas 8,9 and E. jeanselmei 10,11 have been reported in Japan as causative agents of phaeohyphomycosis. In our review, we found that since 2009, the proportion of E. jeanselmei has decreased and the number of other species has increased, especially E .…”
Section: Discussionmentioning
confidence: 99%
“…Itraconazole is the most commonly used antifungal due to its broad spectrum of activity. Four cases treated by voriconazole have also been reported, 7,10,13 and it may be more widely used in the future if studies prove its benefits. Additionally, some cases were treated effectively with hyperthermia 6,9,14 .…”
Section: Discussionmentioning
confidence: 99%
“…
Letter to the Editor Clinical MicrobiologyDear Editor, Thyridium endophyticum, formerly known as Phialemoniopsis endophytica, is an uncommon mold species frequently isolated from the environment or plants [1][2][3]. To our knowledge, only one clinical case of T. endophyticum infection, manifesting as an asymptomatic subcutaneous nodule, has been reported [4]. We present a case of painful tenosynovitis attributed to T. endophyticum in a patient with preexisting medical conditions who underwent synovectomy and repair surgery in the right wrist.
…”
mentioning
confidence: 99%
“…Thyridium (Phialemoniopsis) comprises 33 species, which rarely cause human infection [2]. Most reported human infections by Thyridium species were cutaneous or subcutaneous and typically occurred after trauma or skin injury [4][5][6][7][8][9][10]. Among Phialemoniopsis species, Phialemoniopsis curvatum (formerly Phialemonium curvatum) induces invasive infections, such as endocarditis and fungemia, in immunocompromised patients [5,6].…”
mentioning
confidence: 99%